Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/cells8080808
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty3 and Sprouty4, Two Members of a Family Known to Inhibit FGF-Mediated Signaling, Exert Opposing Roles on Proliferation and Migration of Glioblastoma-Derived Cells

Abstract: Dysregulation of receptor tyrosine kinase-induced pathways is a critical step driving the oncogenic potential of brain cancer. In this study, we investigated the role of two members of the Sprouty (Spry) family in brain cancer-derived cell lines. Using immunoblot analyses we found essential differences in the pattern of endogenous Spry3 and Spry4 expression. While Spry4 expression was mitogen-dependent and repressed in a number of cells from higher malignant brain cancers, Spry3 levels neither fluctuated in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Activated FGFRs localize to the cytoplasm, where they undergo lysosomal degradation or the recycling process, which are partially controlled by CbL-mediated monoubiquitylation or the LIS1/NDE1 complex [ 25 , 32 ]. FGFR signaling may be negatively regulated by MAPK phosphatase 3, Sprouty proteins, and SeF (similar expression to FGF, also known as IL17RD) family members [ 33 , 34 , 35 ] ( Figure 1 ). As the down-regulation of the activated receptors is an important process in order to prevent altered signaling, a defective FGFR ubiquitination system and/or an error in the mitigation pathway could induce aberrant cell growth and malignant transformation [ 36 ].…”
Section: The Fgf/fgfr Systemmentioning
confidence: 99%
“…Activated FGFRs localize to the cytoplasm, where they undergo lysosomal degradation or the recycling process, which are partially controlled by CbL-mediated monoubiquitylation or the LIS1/NDE1 complex [ 25 , 32 ]. FGFR signaling may be negatively regulated by MAPK phosphatase 3, Sprouty proteins, and SeF (similar expression to FGF, also known as IL17RD) family members [ 33 , 34 , 35 ] ( Figure 1 ). As the down-regulation of the activated receptors is an important process in order to prevent altered signaling, a defective FGFR ubiquitination system and/or an error in the mitigation pathway could induce aberrant cell growth and malignant transformation [ 36 ].…”
Section: The Fgf/fgfr Systemmentioning
confidence: 99%
“…SPRY3, an antagonist of the fibroblast growth factor (FGF) pathway [ 120 ], was identified as a therapeutic modulator in a genome-wide CRISPR library screen (64,751 sgRNAs targeting 18,080 genes) performed in an FLT3-mutant AML cell line (MV4-11) treated with a second-generation FLT-3 inhibitor AC220 [ 32 ]. The authors discovered that knockdown of SPRY3 triggers resistance to AC220 by reactivation of the FGF/Ras/ERK signaling pathway.…”
Section: Therapeutic Response Modulatorsmentioning
confidence: 99%
“…8 SPRY4 is ubiquitously expressed in human tissues 11 and is initially known as a tumour suppressor involved in several cancers. SPRY4 is decreased in prostate cancer, 12 non-small-cell lung cancer, 13,14 breast cancer, 15 melanoma, 16 and brain cancer, 17 and overexpression of SPRY4 inhibits cell proliferation, migration, and invasion in these cancers. However, a recent study showed that SPRY4 plays a tumorigenic role in testicular germ cell tumours.…”
Section: Introductionmentioning
confidence: 99%